Bridal favors - Brockway, Connie (New York : Dell, 2002)
To save her aunt's wedding planning business, Evelyn Whyte decides to call in the debt owed to her by Justin Powell, a military hero, by asking him to use his ancestral home for a client's wedding, but she never expects to find herself falling in love.
Keywords: Weddings -- Fiction; Great Britain -- History -- Victoria, 1837-1901 -- Fiction; England -- Social life and customs -- 19th century -- Fiction; Historical fiction; Love stories